2023
DOI: 10.3390/soilsystems7040109
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Fertilizers in Tomato-Grown Soils: Soil Quality, Sustainability, and Carbon/Water Footprints

Angela Maffia,
Federica Marra,
Francesco Canino
et al.

Abstract: This manuscript delves into the pivotal role of sustainable agriculture in addressing environmental challenges and meeting the nutritional demands of a burgeoning global population. The primary objective is to assess the impact of a recently developed eco-friendly fertilizer, denoted as SBO, which arises from the blend of organic and mineral components derived from agricultural waste, sulfur, and residual orange materials. These elements are bound together with bentonite. This study compares SBO with distinct … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…RDI provides adequate water only during critical development periods that may affect yields [15,16]. The effectiveness of water-saving techniques may vary depending on seasonal weather conditions, cultivation site, genotype, fertilization management, and the timing of deficit induction [17][18][19][20]. In Mediterranean and semi-arid environments, DI and RDI would save water resources and increase water productivity [21].…”
Section: Introductionmentioning
confidence: 99%
“…RDI provides adequate water only during critical development periods that may affect yields [15,16]. The effectiveness of water-saving techniques may vary depending on seasonal weather conditions, cultivation site, genotype, fertilization management, and the timing of deficit induction [17][18][19][20]. In Mediterranean and semi-arid environments, DI and RDI would save water resources and increase water productivity [21].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that energy savings and CF reduction can be achieved through water management and treatment technologies, including proactive maintenance to extend the operational life of equipment and aging infrastructure. In [4], the environmental impact of a newly developed eco-friendly fertilizer was assessed, taking into account carbon and water footprints, through LCA. The study aimed to evaluate the implications of the fertilizer on the environment.…”
Section: Introductionmentioning
confidence: 99%